An Evaluation by Midwives and Gynecologists of Treatability of Cervical Lesions by Cryotherapy Among Human Papillomavirus-Positive Women. Issue 4 (1st April 2009) - Gage, Julia C.; Rodriguez, Ana Cecilia; Schiffman, Mark; Adadevoh, Sydney; Alvarez Larraondo, Manuel J.; Chumworathayi, Bandit; Vargas Lejarza, Sandra; Villegas Araya, Luis; Garcia, Francisco; Budihas, Scott R.; Long, Rodney; Katki, Hormuzd A.; et al.
Abstract : Objectives: To estimate efficacy of a visual triage of human papillomavirus (HPV)-positive women to either immediate cryotherapy or referral if not treatable (eg, invasive cancer, large precancers). Methods: We evaluated visual triage in the HPV-positive women aged 25 to 55 years from the 10, 000-woman Guanacaste Cohort Study (n = 552). Twelve Peruvian midwives and 5 international gynecologists assessed treatability by cryotherapy using digitized high-resolution cervical images taken at enrollment. The reference standard of treatability was determined by 2 lead gynecologists from the entire 7-year follow-up of the women. Women diagnosed with histologic cervical intraepithelial neoplasia grade 2 or worse or 5-year persistence of carcinogenic HPV infection were defined as needing treatment. Results: Midwives and gynecologists judged 30.8% and 41.2% of women not treatable by cryotherapy, respectively ( P < 0.01). Among 149 women needing treatment, midwives and gynecologists correctly identified 57.5% and 63.8% ( P = 0.07 for difference) of 71 women judged not treatable by the lead gynecologists and 77.6% and 59.7% ( P < 0.01 for difference) of 78 women judged treatable by cryotherapy. The proportion of women judged not treatable by a reviewer varied widely and ranged from 18.6% to 61.1%. Interrater agreement was poor with mean pairwise overall agreement of 71.4% and 66.3% and κ 's of 0.33 and 0.30 for midwives and gynecologists, respectively. Conclusions: In future "screen-and-treat" cervical cancer prevention programs using HPV testing and cryotherapy, practitioners will visually triage HPV-positive women. The suboptimal performance of visual triage suggests that screen-and-treat programs using cryotherapy might be insufficient for treating precancerous lesions. Improved, low-technology triage methods and/or improved safe and low-technology treatment options are needed.